THE ANALYSIS OF ETHICS AND BUSINESS RELEVANCE IN THE PERSPECTIVE OF ISLAM - Deden Syarif Hidayatulloh (Jurnal Manajemen Indonesia, 2015)
The relation between ethics and business according to Islam is a unity that cannot be separated since a business needs the ethics to perpetuate the profit both in the world and the Hereafter. The ethics is deemed as a set of moral principle which is right from what is wrong. Thus, the ethics is needed in the business. As known, the business is a set of event which involves the businessman. The business in the perspective of Islam is a real work which is extremely honored. The teachings of Islam based on the Al-Qur'an say that it is not allowed to ignore the ethics as the rules which should always be held in performing the business practice to maintain the justice. prosperity, balance and benefit for all, especially to maintain the goodness and security as well as to gain the present and the future advantages